2014
DOI: 10.1097/01.aog.0000447335.80817.94
|View full text |Cite
|
Sign up to set email alerts
|

Does Influenza Vaccination in Pregnancy Reduce the Risk of Preeclampsia?

Abstract: RESULTS: In the base case, compared with metformin, treatment with glyburide resulted in lower incidence of both symptomatic and severe hypoglycemic events, resulting in an incremental benefit of 1.90 quality-adjusted lifeyears (QALYs) and an incremental cost-effectiveness ratio of 4,736 per QALY gained. Univariate sensitivity analysis showed findings to be robust under almost all scenarios. Probabilistic sensitivity analysis showed that there is a 62.7% probability that treatment with glyburide was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A large number of studies on the safety of influenza and pertussis immunization during pregnancy published to date show no evidence for an increase in adverse reactions in pregnant women or their offspring, nor an adverse outcome of pregnancy for either vaccine. [2,3,[15][16][17][18][19][20] Even though the vaccination coverage for pertussis was lower compared to influenza, the reasons for not being vaccinated were similar for both vaccines. Also, there is no evidence that mothers in our study prioritised protection of the baby over their own protection as was shown in a recent on behaviours and attitudes of pregnant women towards vaccination [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies on the safety of influenza and pertussis immunization during pregnancy published to date show no evidence for an increase in adverse reactions in pregnant women or their offspring, nor an adverse outcome of pregnancy for either vaccine. [2,3,[15][16][17][18][19][20] Even though the vaccination coverage for pertussis was lower compared to influenza, the reasons for not being vaccinated were similar for both vaccines. Also, there is no evidence that mothers in our study prioritised protection of the baby over their own protection as was shown in a recent on behaviours and attitudes of pregnant women towards vaccination [37].…”
Section: Discussionmentioning
confidence: 99%
“…Inactivated influenza vaccines and combined diphtheria-tetanus-acellular pertussis vaccines are considered to be safe when given during pregnancy [2,[4][5][6][15][16][17]. Studies on effectiveness on reducing influenza in pregnant women and neonates [1,[18][19] and pertussis in neonates have shown the added value of immunizing pregnant women [11,20,21]. In 2012 the World Health Organization (WHO) recommended immunization against seasonal flu for pregnant women [22] and in 2014 the Strategic Advisory Group of Experts (SAGE) considered that maternal immunization against pertussis was the most cost-effective complementary strategy to prevent pertussis-associated infant mortality [23].…”
Section: Introductionmentioning
confidence: 99%
“…The reduced placental blood flow, resulting in IUGR and fetal hypoxia ( 9 ), has significant long-term implications in the adult. Importantly, women receiving an influenza vaccine during pregnancy have decreased rates of severe preeclampsia ( 10 ). Moreover, preeclampsia significantly increases the risk of future cardiovascular disease in women, with a fourfold to fivefold increased risk of developing hypertension ( 11 ).…”
mentioning
confidence: 99%
“…Safety Successful examples of maternal vaccines, such as influenza IIV, have shown efficacy in reducing maternal, fetal and neonatal morbidity due to infection or other pregnancy complications (Zaman et al, 2008;Omer et al, 2011;Steinhoff et al, 2012;Richards et al, 2013;El-Kady et al, 2014;Legge et al, 2014). Yet many concerns have been raised over maternal vaccination, which need to be addressed by further research.…”
Section: Concerns Over Maternal Vaccinationmentioning
confidence: 99%